2008
DOI: 10.1136/thx.2007.094250
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine computed tomography in paediatric pleural empyema

Abstract: Background: The incidence of empyema in children is increasing worldwide. While there are emerging data for the best treatment options, there is little evidence to support the imaging modalities used to guide treatment, particularly with regard to the role of routine CT scanning. The aims of this study were to develop a radiological scoring system for paediatric empyema and to assess the utility of routine CT scanning in this disease. Methods: Children with empyema were prospectively enrolled over a 3-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 25 publications
1
47
2
3
Order By: Relevance
“…Another relevant observation is that aspiration of bacteria into the lungs resulted in bacterial translocation into the pleural space before histological evidence of pneumonia develops. This could explain why a surprisingly high proportion of cases of empyema have no radiological evidence of pneumonia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant observation is that aspiration of bacteria into the lungs resulted in bacterial translocation into the pleural space before histological evidence of pneumonia develops. This could explain why a surprisingly high proportion of cases of empyema have no radiological evidence of pneumonia (25).…”
Section: Discussionmentioning
confidence: 99%
“…5,21 The initial treatment of all pleural effusion should be the use of antibiotics. For children with small effusions (<10 mm on lateral decubitus chest radiograph or opacification of less than one-fourth of the hemithorax), the choice of broad-spectrum antibiotics, chest radiographs, and good clinical exam should suffice on an outpatient basis.…”
Section: Antibiotics Usementioning
confidence: 99%
“…5 part of it attributed to the debut of the conjugate pneumococcal vaccine. 6 However, rates of parapneumonic effusion (PPE) were noticed to increase 5,[7][8][9] In children younger than 2 years, the PPE rate significantly raised in North America from 3.5 cases per 100 000 children in 1996-1998 to 7.0 cases per 100 000 children in [2005][2006][2007]. 8 During the same periods, the PPE rate increased from 3.7 to 10.3 cases per 100 000 children between the age 2 and 4 years.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric studies showed contradictory conclusion regarding the surgery (including chest tube, VATS and thoracotomy): one study suggested that surgery was not better than thoracocentesis alone [12], and another supported early VATS as a valuable option to avoid prolonged recovery and late thoracotomy compared to conservative treatment [18]. retrospective study specifically reported that empyema associated with NP required a longer hospitalisation than empyema without NP [18], when the sole prospective study showed no difference in hospital length of stay [17], in line with our data. We could not complete the functional follow-up due to the small number of patients, but we found no difference in radiological follow-up between both groups.…”
Section: Discussionmentioning
confidence: 99%